DIGITAL STORYTELLING SEBAGAI METODE CAPTURE PENGETAHUAN ADAT MINANG: PELUANG DAN TANTANGAN DI ERA 5.0 - Madi, Velly Afria; Zalmi, Fadhila Nurul Husna (UIN Imam Bonjol Padang, 2025)
The digital transformation in the era of Society 5.0 encourages the integration of technology with cultural preservation, including efforts to sustain Minangkabau indigenous knowledge traditionally passed down orally. Local wisdom such as pepatah-petitih (proverbs), kaba (epic tales), and pantun (poetic expressions) represents forms of tacit knowledge that are at risk of disappearing due to generational gaps and the lack of systematic documentation. This article explores two key questions: how can digital storytelling (DST) function as a knowledge capture method for Minangkabau traditional knowledge, and what are the opportunities and challenges involved in this process? This study uses a qualitative approach, including literature review, reflective analysis, and case studies of cultural narrative digitization initiatives within local communities and academic libraries. Findings indicate that DST is effective in transforming oral knowledge into digital formats that are both communicative and participatory, especially through the involvement of youth, librarians, and traditional leaders. Major opportunities include community collaboration and the use of digital platforms such as YouTube, institutional repositories, and social media. However, challenges include technological limitations, metadata standardization, and cultural sensitivity in documentation. This study concludes that digital storytelling can serve as a bridge between technology and tradition, provided that it is supported by information literacy policies, community training, and multi-stakeholder collaboration. The model offers strong potential to sustain Minangkabau indigenous knowledge in an increasingly digital and global context.